Microstructure evolution after hot working and heat treatment in 6082 aluminum alloy manufactured by horizontal continuous casting - Mára, Vladimír; Krčil, Jan; Horník, Jakub (Journal of alloys and compounds, 2024)
In this paper, 6082 aluminum alloy manufactured by horizontal continuous casting was subjected to high-temperature plastic deformation under 20–70 % deformation levels with following T6 heat treatment process. Microstructural and phase changes were investigated by light and scanning electron microscopy together with energy dispersive spectroscopy, while grain, grain boundary, dislocation and texture evolution was studied by electron-backscattered diffraction. The results are showing that continuous dynamic recrystallization processes are active during the hot working while influence of static recrystallization is significant only for highest deformation degrees. The abnormally coarse-grained microstructure does locally occur in the subsurface layer after the 70 % deformation and T6 heat treatment. Crystallographic texture components are gradually evolving from the various types (Goss, Brass, D) for the low deformations (up to 40 %) into fiber-type textures (α-fiber, γ-fiber or C2-fiber) for high deformations due to the inhomogeneity of plastic deformation. The formation of AlMnSi dispersoids, CSL-boundaries Σ25b and an increase in fraction of GND, MgSi and Fe-based intermetallic particles was observed during the phase transformation which promotes ongoing nucleation of recrystallization processes. •Formation of special types of grain boundaries promotes recrystallization.•Dispersoids induce abnormal grain growth in the specimen with 70 % deformation.•Stress field near particles create conditions for recrystallization nucleation.•Inhomogeneous plastic deformation creates varying texture components.